2020
DOI: 10.3390/insects11090625
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Density Dynamics of Wolbachia Infection of the Health Pest Paederus fuscipes Curtis (Coleoptera: Staphylinidae)

Abstract: The maternally inherited obligate intracellular bacteria Wolbachia infects the reproductive tissues of a wide range of arthropods and affects host reproduction. Wolbachia is a credible biocontrol agent for reducing the impact of diseases associated with arthropod vectors. Paederus fuscipes is a small staphylinid beetle that causes dermatitis linearis and conjunctivitis in humans when they come into contact with skin. Wolbachia occur in this beetle, but their relatedness to other Wolbachia, their infection dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…Variations in Wolbachia density across developmental stages have been reported in other insects, for instance, Wolbachia density in adults of the beetle Octodonta nipae (Maulik) was higher than that in the immature stages ( Ali et al 2018 ). This correlation between Wolbachia density and developmental stages has also been reported in the wasp H. hebetor ( Bagheri et al 2019 ) and the beetle Paederus fuscipes Curtis ( Ge et al 2020 ). To improve the accuracy of comparison of Wolbachia density among different developmental stage or tissues, future studies using relative qPCR to quantify the internal control gene in Y. flavovittatus are necessary.…”
Section: Discussionsupporting
confidence: 75%
“…Variations in Wolbachia density across developmental stages have been reported in other insects, for instance, Wolbachia density in adults of the beetle Octodonta nipae (Maulik) was higher than that in the immature stages ( Ali et al 2018 ). This correlation between Wolbachia density and developmental stages has also been reported in the wasp H. hebetor ( Bagheri et al 2019 ) and the beetle Paederus fuscipes Curtis ( Ge et al 2020 ). To improve the accuracy of comparison of Wolbachia density among different developmental stage or tissues, future studies using relative qPCR to quantify the internal control gene in Y. flavovittatus are necessary.…”
Section: Discussionsupporting
confidence: 75%
“…As described previously (Ge et al, 2020; Karamipour et al, 2016; Li et al, 2018), qPCR was conducted using M5 HiPer Real‐time PCR Super mix (Mei5 Biotechnology, Beijing, China) to evaluate the relative density of PPB between males and females. Following these studies, the relative abundance of the bacterial gene (i.e., ketosynthase gene of PPB) was analysed using the comparative 2 −ΔΔCT method for gene expression normalization to the endogenous reference gene (i.e., β‐actin) of Paederus fuscipes .…”
Section: Methodsmentioning
confidence: 99%
“…Following these studies, the relative abundance of the bacterial gene (i.e., ketosynthase gene of PPB) was analysed using the comparative 2 −ΔΔCT method for gene expression normalization to the endogenous reference gene (i.e., β‐actin) of Paederus fuscipes . This result is synonymous with the number of PPB per host cell (Ge et al, 2020). The amplification efficiency of the primer pairs was assessed by using a CFX96™ real‐time PCR detection system from Bio–Rad.…”
Section: Methodsmentioning
confidence: 99%
“…The co-occurrence of these two genera was also described in other insect’s gut microbiome like the cricket Gryllus veletis [ 78 ], although Pseudomonas was considered as a probable pathogen that varied its proportion with seasonality and according to Wolbachia ´s abundance. Interestingly, Ge et al, [ 79 ] found similar proportion of Pseudomonas and Wolbachia in the reproductive system of Paederus fuscipes (coleoptera) , where Pseudomonas was found to contribute to the defense from predators thanks to the production of a toxic compound (Pederin), without decreasing the performance of the hosts. Moreover, Wolbachia was found to cope with adverse conditions triggered by Pseudomonas .…”
Section: Discussionmentioning
confidence: 99%